2020
DOI: 10.1002/jsfa.10710
|View full text |Cite
|
Sign up to set email alerts
|

Production of phenolic compounds and antioxidant activity via bioconversion of wheat straw by Inonotus obliquus under submerged fermentation with the aid of a surfactant

Abstract: BACKGROUNDThis study investigated the effect of surfactants on wheat straw biodegradation and the growth‐associated generation of exo‐ and endo‐phenolic compounds (EPC and IPC) and antioxidant activity expression by liquid‐cultured Inonotus obliquus, an edible and medicinal mushroom, also known as a white rot fungus. Changes in the chemical composition and multiscale structure of wheat straw, in the production and activity of EPC and IPC and in individual flavonoids were analyzed.RESULTSFungal pretreatment dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The experimental results indicated M. importuna could yield a wide variety of phenolics. Phenolics are the vital chemical ingredient of some culinary and medicinal mushroom, such as Phellinus pini [ 25 ], Flammulina velutipes [ 26 ], Inonotus obliquus [ 27 ], Ganoderma lucidum [ 28 ], Pleurotus citrinopileatus [ 29 ], Hypsizygus marmoreus [ 30 ], Porodaedalea chrysoloma [ 31 ], Antrodia cinnamomea [ 32 ], and Tuber indicum [ 33 ], etc. Phenolics exhibit antioxidant activity and provide health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results indicated M. importuna could yield a wide variety of phenolics. Phenolics are the vital chemical ingredient of some culinary and medicinal mushroom, such as Phellinus pini [ 25 ], Flammulina velutipes [ 26 ], Inonotus obliquus [ 27 ], Ganoderma lucidum [ 28 ], Pleurotus citrinopileatus [ 29 ], Hypsizygus marmoreus [ 30 ], Porodaedalea chrysoloma [ 31 ], Antrodia cinnamomea [ 32 ], and Tuber indicum [ 33 ], etc. Phenolics exhibit antioxidant activity and provide health benefits.…”
Section: Resultsmentioning
confidence: 99%
“… Zhao et al (2021) identified flavonoids, including gallic acid, ferulic acid, flavonoids epicatechin-3-gallate, epigallocatechin-3-gallate, naringin, rutin, naringenin, phelligridin G, inoscavin B, and davallialectone, from the ethanol extract of I. obliquus . Moreover, they showed that cultivating I. obliquus on wheat straw led to increased levels of inoscavin B and davallialectone.…”
Section: Biologically Active Secondary Metabolites Produced By White-...mentioning
confidence: 98%
“…Therefore, attempts have been made to increase the production of phenolics and flavonoids by I. obliquus through different treatment processes to enhance its antioxidant activities. For example, Zhao et al ( 2021 ) reported that wheat straw culture increased the accumulation of inoscavin B ( 69 ) and davallialactone ( 71 ), while lignocellulose degradation enhanced the generation of flavonoids ECG ( 65 ), EGCG ( 66 ), rutin ( 73 ), and naringin ( 74 ), thereby augmenting I. obliquus’ antioxidative properties.…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%